Macrophage scavenger receptor a promotes tumor progression in murine models of ovarian and pancreatic cancer. - Neyen, C; Plüddemann, A; Mukhopadhyay, S; Maniati, E; Bossard, M; Gordon, S; Hagemann, T (2013)
Alternatively activated macrophages express the pattern recognition receptor scavenger receptor A (SR-A). We demonstrated previously that coculture of macrophages with tumor cells upregulates macrophage SR-A expression. We show in this study that macrophage SR-A deficiency inhibits tumor cell migration in a coculture assay. We further demonstrate that coculture of tumor-associated macrophages and tumor cells induces secretion of factors that are recognized by SR-A on tumor-associated macrophages. We tentatively identified several potential ligands for the SR-A receptor in tumor cell-macrophage cocultures by mass spectrometry. Competing with the coculture-induced ligand in our invasion assay recapitulates SR-A deficiency and leads to similar inhibition of tumor cell invasion. In line with our in vitro findings, tumor progression and metastasis are inhibited in SR-A(-/-) mice in two in vivo models of ovarian and pancreatic cancer. Finally, treatment of tumor-bearing mice with 4F, a small peptide SR-A ligand able to compete with physiological SR-A ligands in vitro, recapitulates the inhibition of tumor progression and metastasis observed in SR-A(-/-) mice. Our observations suggest that SR-A may be a potential drug target in the prevention of metastatic cancer progression.